Kinerja Dana Pihak Ketiga Terhadap Penyaluran Kredit Pada PT BPR Eka Bumi Artha Di Lampung - Wangsit Supeno (LPPM Universitas Bina Sarana Informatika, 2022)
PT BPR Eka Bumi Artha is one of the Rurar Bank that has the largest number of assets in Indonesia operating in Lampung, is considered successful in facing bpr business challenges, and is able to get through difficult conditions during the Covid-19 pandemic in 2020-2021. This study raises the issue of the development of the performance of the provision of third-party funds collected in the form of savings deposits and time deposits, the performance of lending when PT BPR Eka Bumi Artha faced the challenges of competition and unstable economic conditions during the period 2018, 2019, 2020 and 2021. The purpose of this study is to determine the performance of the provision of third party funds in the form of deposits, credit distribution and the performance of the use of third party deposit funds for credit distribution in the position of December 2018, 2019, 2020 and 2021. The research method used is descriptive qualitative with trend analysis techniques on the financial performance of third-party deposits, and also on the performance of credit distribution of PT BPR Eka Bumi Artha whose data is sourced from the financial statements published by BPR on the Financial Services Authority website in December 2018, 2019, 2020 and 2021. The results showed that there was a positive performance development towards the collection of third party funds and credit disbursements in the position of December 2018, 2019, 2020 and 2021. The results of this study also show that the performance of lending over the past four years has averaged 54.20% sourced from third-party deposit funds in the form of savings and credit, the rest of which is financed by other sources of funds.